(untitled) (Revista de Psicología, 2019)
The objective of this paper was to prove the existence of Vital Exhaustion (VE) in patients with Primary Hypothyroidism (PH), if PH treatment modifies VE, and if there is an association between TSH and VE response to treatment. These were grouped taking into account clinical similarities between VE and PH and the implied cardiovascular risk. In a sample of 31 women with PH, the VE and TSH pre and post PH treatment were measured. Afterwards, the relationship between TSH level and VE response was studied. Conclusions: The majority of patients having PH showed VE, which was reverted after PH treatment. There is a Group of patients in which there is a persistence of the VE value after treatment and the TSH value is greater than in those patients where VE reverts.